(untitled) (International relations and international law Journal, 2018)
This article is devoted to studying of interesting phenomenon of the bank activity based on Islamic principles and representing potentially possible alternative to the financial system dominating in the world. The phenomenon of Islamic banks which fundamental difference is refusal of loan percent, is poorly studied in domestic literature. Article represents attempt of theoretical consideration of Islamic model of banking and gives the developed idea of principles and main features of Islamic banks, their differences from traditional model of banking. In article used models of Islamic banking, two-level mudaraba, single-level mudaraba and Islamic bank as the agent are also considered. Key words: Islamic banking, Islamic financing, two-level mudaraba, single-level mudaraba, Islamic bank.